2019
DOI: 10.1071/rd18502
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cytochrome oxidase activity and increased protein tyrosine phosphorylation of mitochondria-rich fractions of buffalo (Bubalus bubalis) spermatozoa after a cycle of freezing and thawing

Abstract: The motility and fertility of mammalian spermatozoa are compromised when they are cryopreserved. Sperm mitochondrial proteins play a vital role in conferring motility. However, the effects of cryopreservation on mitochondria-specific proteins remain primarily unexplored in domestic animals, including buffaloes, so the present study aimed to evaluate this issue. Mitochondria were isolated from both non-cryopreserved and cryopreserved buffalo spermatozoa by sonication followed by sucrose density gradient ultrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…1). These findings reinforce the theory that the mitochondria are specially compromised as consequence of cryopreservation as seen in the functional analysis in our study, and are in the origin of the accelerated senescence of spermatozoa surviving freezing and thawing [6,16,18,23,24,27,[59][60][61]. Also, enrichment analysis of pathways confirmed that the stallion sperm metabolism and redox proteome are dramatically impacted by cryopreservation.…”
Section: Discussionsupporting
confidence: 90%
“…1). These findings reinforce the theory that the mitochondria are specially compromised as consequence of cryopreservation as seen in the functional analysis in our study, and are in the origin of the accelerated senescence of spermatozoa surviving freezing and thawing [6,16,18,23,24,27,[59][60][61]. Also, enrichment analysis of pathways confirmed that the stallion sperm metabolism and redox proteome are dramatically impacted by cryopreservation.…”
Section: Discussionsupporting
confidence: 90%